The organization of African unity and regional disputes, 1963-74: a review - Hossain, Ishtiaq (Centre for Administrative Studies, 1981)
This paper purports to examine the conflict management activities of the OAU during 1963-74, the first decade of its existence. A systematic study of the constitutional powers of the OAU relating to settlement of disputes among its members; handling of various disputes by the OAU and an analysis of the degree of support it received from its member-states while solving the disputes will enable us to make an assessment of the role'of the OAU in solving conflicts among its members.